THE IMPACT OF MIGRATION ON THE ECONOMY OF GERMANY IN THE CONDITIONS OF RUSSIAN AGGRESSION AGAINST UKRAINE - Yakubovskiy, S. O.; Rodionova, T. A.; Moroz, D. M. (The actual problems of regional economy development, 2024)
The study is focused on identifying features and changes in the dynamics of development of the main economic indicators of Germany in recent years during the full-scale invasion of Russia into Ukraine and determining the impact of the influx of migrants from Ukraine on the German economy. The main purpose of the article is to identify and evaluate the socio-economic consequences of the influx of migrants for the German economy. The results of the analysis of the dynamics of the net inflow of migrants to Germany indicate that in 2022 it increased several times, which is clearly related to the full-scale war of Russia against Ukraine. At the same time, already in 2023, the net inflow of migrants to Germany has almost halved compared to the previous year. The results of the conducted research indicate that during 2022-2023, despite the large amount of aid to Ukraine and the costs of maintaining Ukrainian refugees, a gradual decrease in the deficit of the German state budget was observed. A similar trend was observed with the ratio of public debt to GDP in Germany, which reached its maximum value in 2021 after significant budget expenditures to overcome the consequences of the COVID-19 pandemic, and in 2022-2023, despite the costs associated with Russia's aggression against Ukraine, the ratio of Germany's public debt to GDP gradually decreased. Thus, it can be confidently asserted that the influx of Ukrainian refugees in 2022- 2023 did not lead to an increase in Germany's budget deficit and the ratio of its public debt to GDP. The main factor that led to a drop in Germany's real GDP in 2023 was the high level of inflation, which was caused by the introduction of anti-Russian sanctions in the EU countries in general and Germany in particular, which significantly limited the volume of energy and raw material trade between Russia and the EU with Germany, and forced German manufacturers to replace products from Russia with more expensive goods from other regions of the world, in particular the USA. At the same time, these economic losses of Germany from anti-Russian sanctions will contribute to reducing the energy intensity of its economy in the future. The results of the study show that the influx of Ukrainian migrants to Germany not only does not pose any financial, cultural and social risks for the country, but, on the contrary, contributes to economic growth in Germany and a partial solution to the demographic crisis.